Practical holism and nomadic thought - Pereda, Carlos 1944- (Lexington Books, 2023)
"This book presents practical holism as a framework for understanding the ways in which our society and individual lives are affected by moral, legal, political, economic, and other considerations. Only nomadic thought is able to capture the interactions among all those crucial aspects"--
Keywords: Transgression; Holismus; Sozialphilosophie; Holism; Transgression (Ethics); Holisme; holism